Memahami Konflik Bougainville di Papua Nugini: Analisis Kronologi, Aktor, Motivasi dan Penyebab Konflik - Paulus RT Paramma; Maria Lewuk; Robinhot Sagala; Imelda Elosak (Cenderawasih University, 2021)
The Bougainville civil war is perhaps the most protracted conflict, attracting attention from the PNG government and the international community. This article aims to examine the analysis of the conflict in Bougainville between 1988 and 1998, thereby lessons learned can be taken for conflict prevention worldwide today. This study used a model analysis approach introduced by Fisher et al. and popularized by Lisa Schrich, namely when (timeline), why (motivation), who (actor), and what (cause and effect). The results indicate: 1) PNG government failed to anticipate unexpected events; 2) several factors contributed to the Bougainville conflict, including the division of the colonies and the geographical location of Bougainville, cultural differences and the identity of the Bougainvillean people, economic factors, inequality in mining distribution; 3) the main actors identified were the PNG Government, BCL, and BRA as parties to the conflict, while actors determined to defuse the conflict in Bougainville included the United Nations, Australia, New Zealand, and women's groups; 4) PNG is a sovereign state interested in political and economic control, while the BRA demands participation, freedom, and justice.KEYWORDSBougainville Conflict; Bougainville Revolutionary Army; Papua New Guinea